1986
DOI: 10.1001/archotol.1986.03780100031003
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Noise and Aspirin in the Chick Basilar Papilla: Noise and Aspirin Toxicity

Abstract: \s=b\The possible synergism between noise and aspirin for causing cochlear damage was examined histologically. Six chicks fed aspirin for five days and five chicks fed a normal diet only were paired and placed in sound chambers. They were exposed to a 1500-Hz tone at 115 dB sound pressure level for eight hours. The mean serum salicylate level just before noise exposure was 24 mg/dL (1.74 mmol/L). Ten days later they were killed, and the temporal bones were processed. Hair cell counts were made at 100-\g=m\m in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…as determined in the present study in chicks are not found collectively in the literature concerning avian species (Davis and Westfall 1972;Lambert et al 1986;De Backer 2002, 2003;Neirinckx et al 2010). The plasma half-life of acetaminophen ranges between 1-4 h across various species which could increase in cases of overdose (St. Omer and Mohammad 1984;Bannwarth and Pehourcq 2003;Neirinckx et al 2010).…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations
“…as determined in the present study in chicks are not found collectively in the literature concerning avian species (Davis and Westfall 1972;Lambert et al 1986;De Backer 2002, 2003;Neirinckx et al 2010). The plasma half-life of acetaminophen ranges between 1-4 h across various species which could increase in cases of overdose (St. Omer and Mohammad 1984;Bannwarth and Pehourcq 2003;Neirinckx et al 2010).…”
Section: Resultscontrasting
confidence: 63%
“…Neirinckx et al (2010) reported the pharmacokinetics parameters of acetaminophen in five-week old chickens after intravenous and oral administration (10 mg/kg). Comparing the findings of the latter studies in the chicken (Davis and Westfall 1972;Lambert et al 1986;De Backer 2002, 2003;Neirinckx et al 2010) with those of the present one in chicks, the variations in absolute pharmacokinetic values could be attributed to the differences in the dosage, route of administration, dosage form and formulation as well as the age of the birds De Backer 2002, 2003;Machin 2005;Hawkins and Paul-Murphy 2011).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Several studies have found that salicylate protects against ototoxicity and noise-induced hearing loss (Chen et al, 2007; Kopke et al, 2000; Li et al, 2002; Sha et al, 1999; Sha et al, 2006; Yamashita et al, 2005). In contrast, others have reported that salicylate fails to protect against noise-induced hearing loss (Lambert et al , 1986; Spongr et al , 1992) or that salicylate exacerbates temporary noise-induced hearing loss in humans (McFadden et al, 1984b). …”
Section: Discussionmentioning
confidence: 97%